Supported IrOx catalyst as well as preparation method and application thereof

By introducing alkali metal salts into the supported IrOx catalyst, the long-range order of iridium oxide particles is broken and the particle growth is restricted through heat treatment, the problem of difficult to take into account the activity and stability of the existing supported iridium-based catalysts is solved, and a high-activity and stability is achieved. It is suitable for proton exchange membrane electrolysis hydrogen production technology.

CN119663362APending Publication Date: 2025-03-21CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411979157.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing supported iridium-based catalysts have problems that are difficult to take into account in improving activity and stability, and the support is poorly conductive, which limits the performance expression of the catalyst.

Method used

A supported IrOx catalyst is used, which includes an oxide support and an active component supported on the support. The active component includes Ir element and amorphous IrOx coated on the surface of Ir element. The crystal structure of IrOx is long-range disordered and short-range ordered. By introducing alkali metal salts, the long-range order of iridium oxide particles is broken, and the alkali metal salt is in a coated state during the heat treatment process, which assists the oxidation of the catalyst, limits particle growth and increases the active area of ​​the catalyst.

Benefits of technology

The high activity and stability of the supported IrOx catalyst are achieved, the performance of the proton exchange membrane electrolytic hydrogen production anode catalyst is improved, and the preparation method is convenient for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a supported IrOx catalyst as well as a preparation method and application thereof. The supported IrOx catalyst comprises an oxide carrier and an active component supported on the carrier, the active component comprises an Ir elementary substance and amorphous IrOx coated on the surface of the Ir elementary substance; and the crystal structure of the IrOx is long-range disordered and short-range ordered. The preparation method of the supported IrOx catalyst is convenient to implement, high in reproducibility and beneficial to industrial preparation and production, gram-level batch preparation can be achieved under the laboratory condition, and possibility is provided for large-scale preparation of the low-cost, high-activity and high-stability proton exchange membrane water electrolysis hydrogen production anode catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrolytic water oxygen evolution, and specifically relates to a loaded IrO x Catalyst, preparation method and application thereof. Background Art

[0002] The technology of hydrogen production by water electrolysis has the characteristics of green environmental protection, flexible production and high product purity, especially the proton exchange membrane water electrolysis (PEMWE) technology, whose excellent volatility response ability makes it the main direction of hydrogen production from renewable energy sources such as photovoltaics and wind power. The process of PEM water electrolysis can usually be divided into two half reactions, the oxygen evolution reaction (OER) at the anode and the hydrogen evolution reaction (HER) at the cathode. Compared with the generation of hydrogen, the generation reaction of oxygen is a four-electron transfer process with more complex conditions and higher energy required. Therefore, the anode catalyst plays a decisive role in the efficiency of hydrogen production, and it is necessary to further develop efficient OER catalysts. At present, Ir-based catalysts are the most advanced oxygen evolution reaction electrocatalysts, but their high cost and low intrinsic activity are not conducive to the large-scale application of PEMWE technology. Therefore, how to improve the activity and stability of Ir-based catalysts has attracted widespread attention from researchers.

[0003] In recent years, it has been found that amorphous iridium oxide has excellent water oxidation activity, but poor stability, while heat-treated Ir nanoparticles or low-crystallinity IrO x Can be transformed into high crystallinity IrO 2 , the structure is more stable, which can effectively inhibit the inactivation of active sites under working conditions, but it will be accompanied by a decrease in activity.

[0004] Based on this, the literature (Shi Z, Li J, Jiang J, et al. Enhanced Acidic Water Oxidation by Dynamic Migration of Oxygen Species at the Ir / Nb 2 O 5−x Catalyst / Support Interfaces[J]. Angewandte Chemie International Edition, 2022, 61(52):e202212341.) 2 O 5-x The preparation and research of the catalyst revealed that dynamic oxygen migration between the carrier and iridium oxide can avoid dissolution caused by excessive oxidation of Ir under high current density, thereby avoiding the loss of active sites and ensuring long-term stable operation of the catalyst.

[0005] Literature (Wu Y, Guo C, Yao R, et al. Modulating Carrier Oxygen Vacancies to Enhance Strong Oxide-Support Interaction in IrO 2 / Nb 2 O 5 -x Catalysts for Promoting Acidic Oxygen Evolution Reaction[J]. Advanced Functional Materials, 2024, 2410193.) Oxygen vacancies are created based on plasma defect engineering, which enhances the interaction between the carrier and iridium oxide. At the same time, the strong oxide-carrier interaction induces charge transfer from the carrier to IrO 2 The excessive oxidation of Ir is inhibited, thus improving the activity and stability of the catalyst.

[0006] The above studies show that for supported iridium-based catalysts, the presence of carriers can make nanoparticles highly dispersed, effectively avoiding their agglomeration, thereby exposing more active sites, but at the same time accompanied by lower electrical conductivity, resulting in difficulties in expressing the performance of the catalyst. In addition, the interaction between the carrier and iridium oxide only occurs at the interface between the two, with a limited scope, and there is a certain limit to the improvement of stability. It can be seen that the current supported iridium-based catalysts still have the problem of being difficult to have both activity and stability. Summary of the invention

[0007] In view of this, the object of the present invention is to provide a loaded IrO x Catalyst and its preparation method and application. The supported IrO x The catalyst can express high catalytic activity and stability.

[0008] To achieve this object, the present invention provides the following technical solutions:

[0009] In a first aspect, the present invention provides a loaded IrO x (x is 1-2) a catalyst, comprising an oxide carrier and an active component loaded on the carrier; the active component comprises an Ir element and an amorphous IrO coated on the surface of the Ir element x ; The IrO x The crystal structure is long-range disorder and short-range order.

[0010] Preferably, the oxide carrier is selected from any one or more of titania, zirconium oxide, titanium dioxide, niobium oxide, tantalum oxide, cerium oxide or antimony-doped tin oxide.

[0011] Preferably, the supported IrO x The content of Ir element in the catalyst is 20~60 wt%.

[0012] Preferably, the supported IrO x The particle size of the catalyst ranges from 50 to 100 nm, with an average particle size of 68.7 nm.

[0013] Preferably, the IrO x The particle size range is 0.5~1.75 nm, and the average particle size is 1.13 nm.

[0014] In a second aspect, the present invention provides a loaded IrO x The method for preparing a catalyst comprises the following steps:

[0015] S1: a mixture of an Ir source, an oxide carrier, a surfactant and a solvent is subjected to a heating reflux method, a molten salt method or a solvothermal method to obtain an oxide carrier with Ir nanoparticles loaded on the surface;

[0016] S2: Mixing the oxide carrier loaded with Ir nanoparticles on the surface with an alkali metal salt to obtain a precursor, and then heat treating the precursor to obtain a loaded IrO x catalyst.

[0017] Preferably, the Ir source is selected from any one or more of potassium chloroiridate, sodium chloroiridate, chloroiridic acid, iridium acetylacetonate, iridium chloride or iridium acetate.

[0018] Preferably, the oxide carrier includes any one or more of titania, zirconium oxide, titanium dioxide, niobium oxide, tantalum oxide, cerium oxide or antimony-doped tin oxide.

[0019] Preferably, the surfactant includes any one or more of decyltrimethylammonium bromide, dodecyltrimethylammonium chloride, sodium dodecylbenzenesulfonate, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide or dioctadecyldimethylammonium chloride.

[0020] Preferably, the solvent includes any one or more of ethylene glycol, propylene glycol, butylene glycol, pentylene glycol, glycerol, diethylene glycol, tetraethylene glycol or tetraethylene glycol.

[0021] Preferably, the alkali metal salt includes any one or more of lithium salt, sodium salt or potassium salt; the lithium salt includes any one or more of lithium nitrate, lithium chloride, lithium hydroxide, lithium sulfate or lithium carbonate; the sodium salt includes any one or more of sodium nitrate, sodium chloride, sodium hydroxide, sodium sulfate or sodium carbonate; the potassium salt includes any one or more of potassium nitrate, potassium chloride, potassium hydroxide, potassium sulfate or potassium carbonate.

[0022] Preferably, the mass ratio of the iridium element in the Ir source to the oxide carrier is (0.2-0.6):

[0023] Preferably, the molar ratio of the iridium element in the Ir source to the surfactant is 1:(0-8).

[0024] More preferably, the molar ratio of the iridium element in the Ir source to the surfactant is 1:(2-4).

[0025] Preferably, the ratio of iridium element in the Ir source to the solvent is (1-150) mg:10 mL.

[0026] Preferably, the mass ratio of the precursor to the alkali metal salt is 20 mg:(0.1~5) g.

[0027] Preferably, in the heating reflux method, the temperature is heated to 120-180° C. and the reflux time is 2-5 h.

[0028] Preferably, the atmosphere of the heat treatment is selected from nitrogen, argon, air, oxygen or carbon dioxide.

[0029] Preferably, the heat treatment is performed at a temperature of 200-400° C. and for a time of 10-120 min.

[0030] Preferably, the heating rate during the heat treatment is 1-10 °C min -1 .

[0031] In a third aspect, the present invention provides a supported IrO x Application of catalysts in proton exchange membrane water electrolysis to produce hydrogen.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The present invention provides another type of loaded IrO x The catalyst comprises an oxide carrier and an active component loaded on the carrier; the active component comprises an Ir element and an amorphous IrO coated on the surface of the Ir element. x ; The IrO x The crystal structure of (x is between 1 and 2) is long-range disorder and short-range order.

[0034] In the present invention, long-range disorder refers to the fact that the atomic and molecular arrangement of a substance is irregular and does not show periodicity within a larger spatial scale. XRD depends on the long-range order of the substance. The absence of the characteristic peak of iridium in the spectrum proves that IrO x Long-range disorder (see Figure 1Short-range order refers to the regular arrangement of atoms or molecules within a small local space. The more regular lattice fringes seen in HRTEM prove that IrO x Short-range order (see Figure 4 ).

[0035] Specifically, in the preparation method of the present invention, by introducing an alkali metal salt into the precursor, the alkali metal salt can be coated on the surface of the generated Ir nanoparticles. During the heat treatment process, the existing alkali metal ions can be embedded in the IrO x In the lattice, it destroys the long-range order of iridium oxide particles, making them present an amorphous form on a macroscopic level, which is conducive to the expression of catalyst activity. In addition, the alkali metal salt coexists with the catalyst in the form of coating and dispersion during the heat treatment process, which assists oxidation while limiting the growth of iridium nanoparticles, presenting a state of lattice compression on a microscopic level. Smaller particles make the active area of ​​the catalyst higher, which is conducive to the expression of catalyst activity; and the iridium oxide after heat treatment is not completely oxidized. The amorphous iridium oxide on the outer layer is coated on the surface of the Ir single substance, which plays a protective role at high oxidation potential to prevent it from dissolving and dissolving. The Ir single substance on the inner layer can donate electrons to the outer layer to prevent it from being deactivated due to excessive oxidation. The synergistic effect of the two promotes the supported IrO x When the catalyst is used as an anode catalyst in proton exchange membrane water electrolysis, it can express high catalytic activity and stability.

[0036] In addition, the above-mentioned loaded IrO x The catalyst preparation method is easy to implement and has strong reproducibility, which is conducive to industrial preparation and production. Gram-level batch preparation can be achieved under laboratory conditions, providing the possibility for large-scale preparation of low-cost, high-activity and high-stability proton exchange membrane water electrolysis hydrogen production anode catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The supported IrO prepared in Example 1 of the present invention x XRD pattern of anode catalyst for hydrogen production by proton exchange membrane water electrolysis;

[0038] Figure 2 The supported IrO prepared in Example 1 of the present invention x XPS spectrum of the anode catalyst for hydrogen production by proton exchange membrane water electrolysis;

[0039] Figure 3 The supported IrO prepared in Example 2 of the present invention x TEM image and particle size statistics of the anode catalyst for hydrogen production from water by proton exchange membrane electrolysis;

[0040] Figure 3 (a) is the TEM image, Figure 3(b) is the particle size statistics result diagram;

[0041] Figure 4 The supported IrO prepared in Example 2 of the present invention x HRTEM image of the anode catalyst for hydrogen production by proton exchange membrane water electrolysis;

[0042] Figure 4 (a) is a HRTEM image with Ir lattice spacing. Figure 4 (b) is marked with IrO 2 HRTEM images of lattice spacing;

[0043] Figure 5 The supported IrO prepared in Example 3 of the present invention x Polarization curve of PEMWE single cell assembled with anode catalyst for hydrogen production by proton exchange membrane electrolysis of water;

[0044] Figure 6 The supported IrO prepared in Example 4 of the present invention x Polarization curve of PEMWE single cell assembled with anode catalyst for hydrogen production by proton exchange membrane electrolysis of water;

[0045] Figure 7 The supported IrO prepared in Example 5 of the present invention x SEM images of the anode catalyst for hydrogen production by proton exchange membrane electrolysis at different scales;

[0046] in, Figure 7 (a) is a SEM image with a scale of 5 μm. Figure 7 (b) is a SEM image with a scale of 2 μm. Figure 7 (c) is a SEM image with a scale of 4 μm. Figure 7 (d) is the SEM image with a scale of 1 μm;

[0047] Figure 8 The supported IrO prepared in Example 6 of the present invention x Polarization curve of PEMWE single cell assembled with anode catalyst for hydrogen production by proton exchange membrane electrolysis of water;

[0048] Fig. 9 The supported IrO prepared in Example 7 of the present invention x The linear voltammetric curve test results of the anode catalyst for hydrogen production by proton exchange membrane electrolysis under a three-electrode system;

[0049] Fig.10 The supported IrO prepared in Example 8 of the present invention x Polarization curve of PEMWE single cell assembled with anode catalyst for hydrogen production by proton exchange membrane electrolysis of water;

[0050] Fig.11 The supported IrO prepared in Example 8 of the present invention x The constant current stability test results of the PEMWE single cell assembled with the anode catalyst for hydrogen production by proton exchange membrane electrolysis of water;

[0051] Fig.12 The supported IrO prepared in Example 9 of the present invention x EDS spectrum obtained by SEM-EDS testing of the anode catalyst for hydrogen production by proton exchange membrane electrolysis of water;

[0052] Fig.13 The supported IrO prepared in Comparative Example 1 of the present invention x Polarization curve of PEMWE single cell assembled with anode catalyst for hydrogen production by proton exchange membrane electrolysis of water. DETAILED DESCRIPTION

[0053] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0054] In view of the problems in the prior art that the supported iridium oxide catalyst carrier has poor conductivity and it is difficult to balance the catalyst activity and stability, the present invention provides a supported IrO x The catalyst comprises an oxide carrier with high stability and corrosion resistance and an active component loaded on the carrier; the active component comprises an Ir element and an amorphous IrO coated on the surface of the Ir element. x (The value of x is 1~2). x The crystal structure of a substance is long-range disordered and short-range ordered. Long-range disorder means that the arrangement of atoms and molecules of a substance is irregular and does not show periodicity within a larger spatial scale, while short-range order means that atoms or molecules show a regular arrangement within a smaller local spatial range.

[0055] In the present invention, the oxide support surface is loaded with IrO having both high activity and stability. x , where IrO x It has the characteristics of short-range order and long-range disorder. In addition, IrO x The nanoparticles form an intimate contact with the oxide substrate, which is beneficial to maximize the interfacial effect.

[0056] After testing, the loaded IrO x The particle size of the catalyst ranges from 50 to 100 nm, with an average particle size of 68.7 nm. xThe particle size range is 0.5~1.75 nm, and the average particle size is 1.13 nm.

[0057] The present invention also provides a kind of above-mentioned loaded IrO x The method for preparing a catalyst comprises the following steps:

[0058] S1: mixing an Ir source, an oxide support, a surfactant and a solvent to obtain a mixture;

[0059] S2: The mixture is subjected to a heating reflux method, a molten salt method or a solvothermal method to obtain an oxide support with Ir nanoparticles loaded on the surface;

[0060] S3: After mixing the oxide carrier loaded with Ir nanoparticles on the surface with an alkali metal salt, a precursor is obtained, and heat-treated to obtain a loaded IrO x catalyst.

[0061] According to the present invention, firstly, an Ir source, an oxide carrier, a surfactant and a solvent are mixed to obtain a mixture.

[0062] In the present invention, the Ir source is selected from any one or more of potassium chloroiridate, sodium chloroiridate, chloroiridic acid, iridium acetylacetonate, iridium chloride or iridium acetate, preferably chloroiridic acid. 2 IrCl 6 .

[0063] In the present invention, the oxide carrier includes any one or more of titania, zirconium oxide, titanium dioxide, niobium oxide, tantalum oxide, cerium oxide or antimony-doped tin oxide, preferably niobium oxide.

[0064] In the present invention, the surfactant can assist in dispersing the iridium nanoparticles to prevent them from agglomerating, and can specifically include any one or more of decyltrimethylammonium bromide, dodecyltrimethylammonium chloride, sodium dodecylbenzenesulfonate, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide or dioctadecyldimethylammonium chloride.

[0065] The solvent is used to provide a liquid environment, and includes any one or more of ethylene glycol, propylene glycol, butylene glycol, pentanediol, glycerol, diethylene glycol, tetraethylene glycol or tetraethylene glycol, preferably ethylene glycol.

[0066] The present invention has no particular limitation on the sources of the Ir source, oxide carrier, surfactant and solvent, and they may be generally commercially available products.

[0067] In some embodiments of the present invention, the Ir source, the oxide carrier and the surfactant are preferably dispersed into the solvent by ultrasound or ball milling, wherein the mass ratio of the iridium element in the Ir source to the oxide carrier is (0.2-0.6):1, preferably (0.4-0.5):1; the molar ratio of the iridium element in the Ir source to the surfactant is 1:(0-8), preferably 1:(2-4); the ratio of the iridium element in the Ir source to the solvent is (1-150) mg:10 mL, preferably (50-100) mg:10 mL. The time of the above-mentioned ultrasound or ball milling dispersion is controlled at 1-10 h, preferably 5-8 h.

[0068] The present invention can realize the loading of active components on the carrier by heating reflux method (polyol reflux method), molten salt method, solvent thermal method, etc. In some embodiments of the present invention, taking the polyol reflux method as an example, IrO x Load on carrier.

[0069] Exemplarily, the polyol reflux method comprises the following steps: after obtaining the above-mentioned mixture, the mixture is heated, accompanied by condensation reflux, to obtain an oxide carrier with Ir nanoparticles loaded on the surface. In some embodiments of the present invention, the mixture is preferably transferred to an oil bath for heating and condensation reflux. Generally, it is heated to 120-180°C, preferably 150-160°C, and condensed and refluxed at this temperature, and the condensation reflux time is 2-5 h, preferably 3-4 h, and an oxide carrier with Ir nanoparticles loaded on the surface is obtained.

[0070] According to the present invention, it is preferred to uniformly mix an oxide support loaded with Ir nanoparticles on its surface with an alkali metal salt to obtain a precursor. The alkali metal salt includes any one or more of lithium salt, sodium salt or potassium salt; the lithium salt includes any one or more of lithium nitrate, lithium chloride, lithium hydroxide, lithium sulfate or lithium carbonate; the sodium salt includes any one or more of sodium nitrate, sodium chloride, sodium hydroxide, sodium sulfate or sodium carbonate; the potassium salt includes any one or more of potassium nitrate, potassium chloride, potassium hydroxide, potassium sulfate or potassium carbonate.

[0071] In some embodiments of the present invention, the mixing is preferably performed according to a mass ratio of the precursor to the alkali metal salt of 20 mg:(0.1-5) g, more preferably 20 mg:(0.5-3) g.

[0072] In some preferred embodiments of the present invention, the precursor is dried to remove the solvent and then subjected to heat treatment. The drying method can be carried out by means well known to those skilled in the art. In the present invention, the solvent is preferably removed by rotary evaporation.

[0073] Then, according to the present invention, the dried precursor is subjected to heat treatment, and the heat treatment is preferably carried out in a muffle furnace, and the atmosphere can be selected from nitrogen, argon, air, oxygen or carbon dioxide. In the present invention, the heat treatment is preferably heated to 200-400°C, preferably 250-350°C; in this process, a too high heating rate will cause the catalyst to explode, and a too low rate will cause the reaction time to be too long, resulting in a significant increase in time cost. Therefore, the heating rate in the present invention is 1-10°C min -1 , preferably 5~8 ℃ min -1 ; The holding time after heating to the target temperature is 10 to 120 min, preferably 30 to 60 min.

[0074] In some preferred embodiments of the present invention, after the heat treatment is completed, post-treatment steps such as cooling to room temperature, washing and drying are also included.

[0075] It should be noted that in some other technical solutions of the present invention, alkali metal salts can also be used to directly treat the supported IrO x The catalyst can be modified, but the process is relatively complicated.

[0076] The present invention is in the above-mentioned loaded IrO x In the preparation method of the catalyst, alkali metal ions are introduced to break the long-range order of iridium oxide particles, and during the heat treatment process, alkali metal salts are in a coated state to assist the oxidation of the catalyst, which limits the growth of the particles and presents a state of lattice compression. The catalyst has a higher active area, which is conducive to the expression of activity. After heat treatment, the iridium oxide presents a tiny core-shell structure. The outer amorphous iridium oxide can protect the inner iridium element to prevent it from dissolving; the inner iridium element can supply electrons to the outer oxide shell to prevent it from being over-oxidized and causing the catalyst to be deactivated. The synergistic effect of the two improves the stability of the catalyst.

[0077] In summary, the supported IrO prepared by the present invention x Catalyst, comprising an oxide carrier and IrO supported on the carrier x The IrO loaded on the carrier x It includes Ir single substance and amorphous iridium oxide coated on the surface of Ir single substance. x It has a special crystal structure, showing a state of long-range disorder and short-range order. The above results can be verified by the following characterization and testing: XRD results show that the iridium element in the supported IrOx catalyst exists in an amorphous state; Ir 4f XPS data show that the iridium nanoparticles in the catalyst are not completely oxidized to IrO 2 , the iridium element coexists in multiple valence states.

[0078] In the loaded IrOx In the catalyst, if the Ir content is too low, the Ir on the catalyst surface is discontinuous, resulting in difficulty in electron transfer; on the contrary, if the Ir content is too high, the carrier cannot achieve the goal of improving the utilization rate of precious metals. x The content of Ir element in the catalyst is 20~60 wt%, which can ensure that the catalyst has good conductivity and can greatly improve the utilization rate of precious metals.

[0079] Furthermore, the SEM test results showed that the catalyst prepared by the above method showed a spherical particle morphology. The particle size statistics of the TEM test results showed that the average particle size of the prepared catalyst was 1.13 nm. The performance tests in three electrodes and PEMWE single cells showed that the catalyst had good water oxidation activity. The stability test in PEMWE single cells showed that the prepared supported IrO x The catalyst can maintain excellent catalytic activity for a long time, which shows that it has excellent operating stability.

[0080] In summary, the loaded IrO x Compared with the existing commercial proton exchange membrane water electrolysis hydrogen production anode catalyst, the catalyst uses less precious metals, has higher catalytic activity and better stability.

[0081] In order to further illustrate the present invention, the following examples are provided for detailed description. The experimental raw materials used in the following examples of the present invention are all common commercially available products.

[0082] Example 1

[0083] Weigh 2.25 g of commercial Nb 2 O 5 , 10 g CTAB, add 8.93 mL 140 mg mL -1 H 2 IrCl 6 , 500 mL of ethylene glycol, ball-milled and dispersed for 5 h, then transferred to an oil bath, condensed and refluxed at 160 °C for 3.5 h to obtain Ir nanoparticles supported on niobium oxide.

[0084] The above obtained product was mixed with 50 g NaNO 3 Mix well, remove the solvent by rotary evaporation to obtain the precursor; place the precursor in a muffle furnace at 5 ºC min -1 The temperature was raised to 350°C at a rate of 100 °C, maintained for 0.5 h, and cooled naturally to room temperature. The sample was ultrasonically washed with deionized water for 1 h, filtered, washed with deionized water several times to remove excess impurities, and dried to obtain the supported IrO x Anode catalyst for hydrogen production by proton exchange membrane electrolysis of water.

[0085] For the supported IrO x The anode catalyst of proton exchange membrane water electrolysis for hydrogen production was tested by XRD. The results are shown in the attached Figure 1 As shown in the test results, the characteristic peaks of niobium oxide can be clearly seen, but no obvious Ir single substance or IrO 2 The characteristic peaks of iridium indicate that the iridium element in the catalyst prepared by this method exists in an amorphous form, which further proves that the introduction of alkali ions breaks the long-range order of iridium oxide.

[0086] For the supported IrO x The Ir 4f XPS test of the anode catalyst for hydrogen production by proton exchange membrane electrolysis of water was carried out. The results are shown in the attached Figure 2 As shown, compared with commercial IrO 2 It can be seen from the comparison that the prepared catalyst has a higher electron density and the valence state of the Ir element in the catalyst is lower than that of commercial IrO 2 , indicating that iridium was not completely oxidized during the heat treatment.

[0087] Example 2

[0088] Weigh 0.5 g of commercial Nb 2 O 5 , 2.766 g CTAB, add 3.57 mL 140 mg mL -1 H 2 IrCl 6 , 500 mL of ethylene glycol, ball-milled and dispersed for 4 h, then transferred to an oil bath and condensed and refluxed at 160 °C for 3 h to obtain Ir nanoparticles supported on niobium oxide.

[0089] The above obtained product was mixed with 10 g NaNO 3 Mix well, remove the solvent by rotary evaporation to obtain the precursor; place the precursor in a muffle furnace at 5 ºC min -1 The temperature was raised to 300°C at a rate of 100 °C, maintained for 0.5 h, and cooled naturally to room temperature. The product was ultrasonically washed with deionized water for 1 h, filtered, washed with deionized water several times to remove excess impurities, and dried to obtain the supported IrO x Anode catalyst for hydrogen production by proton exchange membrane electrolysis of water.

[0090] For the supported IrO x The anode catalyst of proton exchange membrane water electrolysis for hydrogen production was tested by TEM, and the particle size statistics were calculated, as shown in the attached figure. Figure 3 As shown, Figure 3 (a) is the TEM image, Figure 3 (b) is the particle size statistics. After statistical analysis, the IrOx The average particle size of the nanoparticles is 1.13 nm.

[0091] For the supported IrO x The anode catalyst of proton exchange membrane water electrolysis for hydrogen production was tested by HRTEM, and the lattice spacing was measured. Figure 4 As shown, Figure 4 (a) is a HRTEM image with Ir lattice spacing. Figure 4 (b) is marked with IrO 2 The HRTEM image of lattice spacing shows that the catalyst prepared by this method can simultaneously measure the lattice fringes of elemental iridium and iridium dioxide.

[0092] Example 3

[0093] Weigh 75 mg of commercial Nb 2 O 5 , 284 mg CTAB, add 2.14 mL 35 mg mL -1 H 2 IrCl 6 , 100 mL of ethylene glycol, ball-milled and dispersed for 2.5 h, then transferred to an oil bath and condensed and refluxed at 160 °C for 3 h to obtain Ir nanoparticles supported on niobium oxide.

[0094] The above product was mixed evenly with 1.5 g NaCl, and the solvent was removed by rotary evaporation to obtain a precursor; the precursor was placed in a muffle furnace at 5 ºC min -1 The temperature was raised to 280 °C at a rate of 100 °C, maintained for 0.5 h, and cooled naturally to room temperature. The system was ultrasonically washed with deionized water for 1 h, filtered, washed with deionized water several times to remove excess impurities, and dried to obtain the supported IrO x Anode catalyst for hydrogen production by proton exchange membrane electrolysis of water.

[0095] Using the loaded IrO x The anode catalyst of proton exchange membrane water electrolysis was used as the anode, and a PEMWE single cell was assembled to conduct polarization curve test. The results are shown in the attached figure. Figure 5 As shown, the supported IrO prepared by this method x Has excellent catalytic performance.

[0096] Example 4

[0097] Weigh 75 mg of commercial Nb 2 O 5 , 415 mg CTAB, add 2.14 mL 35 mg mL -1 H 2 IrCl 6, 100 mL of ethylene glycol, ultrasonically disperse for 3 h, then transfer to an oil bath, condense and reflux at 160 °C for 3 h to obtain Ir nanoparticles supported on niobium oxide.

[0098] The above obtained product was mixed with 1.5 g LiNO 3 Mix well, remove the solvent by rotary evaporation to obtain the precursor; place the precursor in a muffle furnace at 5 ºC min -1 The temperature was raised to 280°C at a rate of 100 °C, maintained for 0.5 h, and cooled naturally to room temperature. The system was ultrasonically washed with deionized water for 1 h, filtered, washed with deionized water several times to remove excess impurities, and dried to obtain the loaded IrO x Anode catalyst for hydrogen production by proton exchange membrane electrolysis of water.

[0099] Using the loaded IrO x The anode catalyst of proton exchange membrane water electrolysis was used as the anode, and a PEMWE single cell was assembled to conduct polarization curve test. The results are shown in the attached figure. Figure 6 As shown, the supported IrO prepared by this method x Has excellent catalytic performance.

[0100] Example 5

[0101] Weigh 1 g of commercial Nb 2 O 5 , 5 g CTAB, add 7.14 mL 140 mg mL -1 H 2 IrCl 6 , 500 mL of ethylene glycol, ball-milled and dispersed for 5 h, then transferred to an oil bath, condensed and refluxed at 160 °C for 5 h to obtain Ir nanoparticles supported on niobium oxide.

[0102] The above obtained product was mixed with 20 g NaNO 3 Mix well, remove the solvent by rotary evaporation to obtain the precursor; place the precursor in a muffle furnace at 5 ºC min -1 The temperature was raised to 300°C at a rate, maintained for 10 min, and naturally cooled to room temperature; ultrasonically washed with deionized water for 1 h, filtered, washed with deionized water several times to remove excess impurities, and dried to obtain the supported IrO x Anode catalyst for hydrogen production by proton exchange membrane electrolysis of water.

[0103] For the supported IrO x The SEM test of the anode catalyst for hydrogen production by proton exchange membrane electrolysis of water was carried out. The results are shown in the attached Figure 7 As shown in the figure, the spherical particles are niobium oxide carriers with a relatively uniform size distribution of about 50-100 nm. The iridium particles are very small in size. Figure 3The average particle size is shown, so it is difficult to show the morphology of the iridium particles in the SEM test.

[0104] Example 6

[0105] Weigh 1 g of commercial Nb 2 O 5 , 5 g CTAB, add 7.14 mL 140 mg mL -1 H 2 IrCl 6 , 500 mL of ethylene glycol, ball-milled and dispersed for 5 h, then transferred to an oil bath and condensed and refluxed at 160 °C for 3 h to obtain Ir nanoparticles supported on niobium oxide.

[0106] The above obtained product was mixed with 20 g NaNO 3 Mix well, remove the solvent by rotary evaporation to obtain the precursor; place the precursor in a muffle furnace at 5 ºC min -1 The temperature was raised to 250°C at a rate, maintained for 30 min, and cooled naturally to room temperature; ultrasonically washed with deionized water for 1 h, filtered, washed with deionized water several times to remove excess impurities, and dried to obtain the supported IrO x Anode catalyst for hydrogen production by proton exchange membrane electrolysis of water.

[0107] Using the supported IrO x The anode catalyst of proton exchange membrane water electrolysis was used as the anode, and a PEMWE single cell was assembled to conduct polarization curve test. The results are shown in the attached figure. Figure 8 As shown, the supported IrO prepared by this method x Has excellent catalytic performance.

[0108] Example 7

[0109] Weigh 75 mg of commercial Nb 2 O 5 , 415 mg CTAB, add 2.14 mL 35 mg mL -1 H 2 IrCl 6 , 100 mL of ethylene glycol, ultrasonically disperse for 3 h, then transfer to an oil bath, condense and reflux at 160 ℃ for 3 h to obtain Ir nanoparticles supported on niobium oxide.

[0110] The above obtained product was mixed with 1.2 g KNO 3 , 0.3 g LiNO 3 Mix well, remove the solvent by rotary evaporation to obtain the precursor; place the precursor in a muffle furnace at 5 ºC min -1The temperature was raised to 300°C at a rate of 100 °C, maintained for 0.5 h, and cooled naturally to room temperature. The product was ultrasonically washed with deionized water for 1 h, filtered, washed with deionized water several times to remove excess impurities, and dried to obtain the supported IrO x Anode catalyst for hydrogen production by proton exchange membrane electrolysis of water.

[0111] For the supported IrO x The linear voltammetric curve of the anode catalyst for hydrogen production by proton exchange membrane electrolysis was tested in a three-electrode system. The results are shown in the attached figure. Fig. 9 As shown, the supported IrO prepared by this method x At 10 mA cm -2 The overpotential at the current density is only 261 mV, which is much lower than the overpotential of commercial iridium oxide at the same current density, indicating that the catalyst has excellent catalytic performance.

[0112] Example 8

[0113] Weigh 75 mg of commercial Nb 2 O 5 , 415 mg CTAB, add 2.14 mL 35 mg mL -1 H 2 IrCl 6 , 150 mL of ethylene glycol, and ultrasonically dispersed for 3 h. Then the mixture was transferred to an oil bath and condensed and refluxed at 160 °C for 3 h to obtain Ir nanoparticles supported on niobium oxide.

[0114] The above obtained product was mixed with 1.5 g NaNO 3 Mix well, remove the solvent by rotary evaporation to obtain the precursor; place the precursor in a muffle furnace at 5 ºC min -1 The temperature was raised to 300°C at a rate of 100 °C, maintained for 0.5 h, and cooled naturally to room temperature. The product was ultrasonically washed with deionized water for 1 h, filtered, washed with deionized water several times to remove excess impurities, and dried to obtain the supported IrO x Anode catalyst for hydrogen production by proton exchange membrane electrolysis of water.

[0115] Using the supported IrO x The anode catalyst of proton exchange membrane water electrolysis was used as the anode, and a PEMWE single cell was assembled to conduct polarization curve test. The results are shown in the attached figure. Fig.10 As shown, the supported IrO prepared by this method x Has excellent catalytic performance.

[0116] Using the supported IrO x The anode catalyst of proton exchange membrane electrolysis water production hydrogen production is used as the anode, and a PEMWE single cell is assembled. -2The stability test was carried out under the current density, and the results are shown in the attached Fig.11 As shown in Figure 2, the performance decay rate is only 14.5 μV h after 3000 h of operation. -1 , indicating that the IrO prepared by this method x Has excellent operating stability.

[0117] Example 9

[0118] Weigh 1 g of commercial Nb 2 O 5 , 5 g CTAB, add 7.14 mL 140 mg mL -1 H 2 IrCl 6 , 500 mL of ethylene glycol, ball-milled and dispersed for 5 h, then transferred to an oil bath, condensed and refluxed at 160 °C for 3 h to obtain Ir nanoparticles supported on niobium oxide.

[0119] The above obtained product was mixed with 20 g NaNO 3 Mix well, remove the solvent by rotary evaporation to obtain the precursor; place the precursor in a muffle furnace at 2 ºC min -1 The temperature was raised to 300°C at a rate, maintained for 10 min, and naturally cooled to room temperature; ultrasonically washed with deionized water for 1 h, filtered, washed with deionized water several times to remove excess impurities, and dried to obtain the supported IrO x Anode catalyst for hydrogen production by proton exchange membrane electrolysis of water.

[0120] For the supported IrO x The SEM-EDS test of the anode catalyst for hydrogen production by proton exchange membrane electrolysis of water is shown in the attached figure. Fig.12 As shown, according to the measured element content, it can be known that a catalyst with an iridium loading of 50 wt% was prepared.

[0121] Example 10

[0122] Weigh 75 mg of commercial Ta 2 O 5 , 415 mg CTAB, add 2.14 mL 35 mg mL -1 H 2 IrCl 6 , 150 mL of ethylene glycol, and after ultrasonic dispersion for 3 h, the mixture was transferred to an oil bath and condensed and refluxed at 160 °C for 3 h to obtain Ir nanoparticles supported on tantalum oxide.

[0123] The above obtained product was mixed with 1.5 g NaNO 3 Mix well, remove the solvent by rotary evaporation to obtain the precursor; place the precursor in a muffle furnace at 10 ºC min-1 The temperature was raised to 300°C at a rate of 100 °C, maintained for 0.5 h, and cooled naturally to room temperature. The product was ultrasonically washed with deionized water for 1 h, filtered, washed with deionized water several times to remove excess impurities, and dried to obtain the supported IrO x Anode catalyst for hydrogen production by proton exchange membrane electrolysis of water.

[0124] Embodiment 11

[0125] Weigh 75 mg of commercial Ta 2 O 5 , 415 mg CTAB, 188 mg K 2 IrCl 6 , 150 mL of ethylene glycol, and after ultrasonic dispersion for 3 h, the mixture was transferred to an oil bath and condensed and refluxed at 160 °C for 3 h to obtain Ir nanoparticles supported on tantalum oxide.

[0126] The above obtained product was mixed with 1.5 g NaNO 3 Mix well, remove the solvent by rotary evaporation to obtain the precursor; place the precursor in a muffle furnace at 5 ºC min -1 The temperature was raised to 300°C at a rate of 100 °C, maintained for 0.5 h, and cooled naturally to room temperature. The product was ultrasonically washed with deionized water for 1 h, filtered, washed with deionized water several times to remove excess impurities, and dried to obtain the supported IrO x Anode catalyst for hydrogen production by proton exchange membrane electrolysis of water.

[0127] Comparative Example 1

[0128] Weigh 60 mg of commercial Nb 2 O 5 , 498 mg CTAB, add 2.57 mL 35 mg mL -1 H 2 IrCl 6 , 150 mL ethylene glycol, ultrasonically dispersed for 3 h, then transferred to an oil bath, condensed and refluxed at 160 ° C for 3 h to obtain Ir nanoparticles supported on niobium oxide. The above-obtained product was placed in a muffle furnace and heated at 5 ° C min -1 The temperature was raised to 200 °C at a rate of 100 °C, maintained for 2 h, and cooled naturally to room temperature to obtain supported IrO x Anode catalyst for hydrogen production by proton exchange membrane electrolysis of water.

[0129] The loaded IrO x The anode catalyst of proton exchange membrane water electrolysis was used as the anode, and a PEMWE single cell was assembled to conduct polarization curve test. The results are shown in the attached figure. Fig.13 As shown, the supported IrO prepared by this method xThe higher the degree of oxidation, the larger the particles, which makes the catalyst unable to express its catalytic activity well.

[0130] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A loaded IrO x A catalyst, characterized in that The invention comprises an oxide carrier and an active component loaded on the carrier; the active component comprises an Ir single substance and an amorphous IrO coated on the surface of the Ir single substance. x ; The IrO x The crystal structure is long-range disorder and short-range order, where the value of x is 1~2.

2. The loaded IrO according to claim 1 x A catalyst, characterized in that The oxide carrier is selected from any one or more of titania, zirconium oxide, titanium dioxide, niobium oxide, tantalum oxide, cerium oxide or antimony-doped tin oxide.

3. The loaded IrO according to claim 1 or 2 x A catalyst, characterized in that The supported IrO x The content of Ir element in the catalyst is 20~60 wt%.

4. The loaded IrO according to any one of claims 1 to 3 x A catalyst, characterized in that The supported IrO x The particle size of the catalyst ranges from 50 to 100 nm; The IrO x The particle size range is 0.5~1.75 nm.

5. A loaded IrO as claimed in any one of claims 1 to 4 x The method for preparing a catalyst is characterized in that: The following steps are involved: S1: a mixture of an Ir source, an oxide carrier, a surfactant and a solvent is subjected to a heating reflux method, a molten salt method or a solvothermal method to obtain an oxide carrier with Ir nanoparticles loaded on the surface; S2: Mixing the oxide carrier loaded with Ir nanoparticles on the surface with an alkali metal salt to obtain a precursor, and then heat treating the precursor to obtain a loaded IrO x catalyst.

6. The preparation method according to claim 5, characterized in that: The Ir source is selected from any one or more of potassium chloroiridate, sodium chloroiridate, chloroiridic acid, iridium acetylacetonate, iridium chloride or iridium acetate; The oxide carrier includes any one or more of titania, zirconium oxide, titanium dioxide, niobium oxide, tantalum oxide, cerium oxide or antimony-doped tin oxide; The surfactant includes any one or more of decyltrimethylammonium bromide, dodecyltrimethylammonium chloride, sodium dodecylbenzenesulfonate, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide or dioctadecyldimethylammonium chloride; The solvent includes any one or more of ethylene glycol, propylene glycol, butylene glycol, pentylene glycol, glycerol, diethylene glycol, tetraethylene glycol or tetraethylene glycol; The alkali metal salt includes any one or more of lithium salt, sodium salt or potassium salt; the lithium salt includes any one or more of lithium nitrate, lithium chloride, lithium hydroxide, lithium sulfate or lithium carbonate; the sodium salt includes any one or more of sodium nitrate, sodium chloride, sodium hydroxide, sodium sulfate or sodium carbonate; the potassium salt includes any one or more of potassium nitrate, potassium chloride, potassium hydroxide, potassium sulfate or potassium carbonate.

7. The preparation method according to claim 5 or 6, characterized in that: The mass ratio of the iridium element in the Ir source to the oxide carrier is (0.2-0.6):1; The molar ratio of the iridium element in the Ir source to the surfactant is 1:(0-8); The ratio of iridium element to solvent in the Ir source is (1-150) mg:10 mL; The mass ratio of the precursor to the alkali metal salt is 20 mg:(0.1~5) g.

8. The preparation method according to any one of claims 5 to 7, characterized in that In the heating reflux method, the temperature is heated to 120-180° C. and the reflux time is 2-5 h.

9. The preparation method according to any one of claims 5 to 8, characterized in that The atmosphere of the heat treatment is selected from nitrogen, argon, air, oxygen or carbon dioxide; The heat treatment temperature is 200-400°C and the time is 10-120 min; The heating rate during the heat treatment is 1-10 °C min -1 .

10. The supported IrO according to any one of claims 1 to 4 x Catalyst or the supported IrO prepared by the preparation method according to any one of claims 5 to 9 x Application of catalysts in proton exchange membrane water electrolysis to produce hydrogen.

Citation Information

Cited By

  • Mixed molten salt method for rapidly preparing short-range ordered iridium oxide for PEM electrolyzed water

    CN119977008A

  • Rapid preparation of short-range ordered iridium oxide by a mixed molten salt method for PEM water electrolysis

    CN119977008B

  • Tin dioxide loaded amorphous cobalt iridium oxide catalyst, preparation method thereof and application of catalyst in proton exchange membrane electrolyzed water

    CN121700444A